Analysis on Innovative Models of Strategic Marketing Management for E-Commerce Enterprises under the Internet of Things: Case Study in China - Alqahtani, Khaled Mohammed (The Arab Journal of Administration, 2024)
The strategic marketing management of traditional e-commerce enterprises can lead to user experience being limited by technology and platforms, reducing user purchase intention and loyalty. The Internet of Things (IoT) technology can be used to innovate the strategic marketing management of traditional e-commerce enterprises and overcome the shortcomings of traditional e-commerce marketing management. By collecting a large amount of data through sensors and other IoT devices, including user behavior data, logistics data, etc., this study conducted comprehensive analysis and deep mining of the data. It provided an in-depth understanding of user needs and purchasing behavior patterns to develop personalized marketing plans. Through the connection of smart wearable devices, this provided users with personalized product experiences and customized services. Finally, this study regularly evaluated and offered feedback on marketing effectiveness, and continuously optimized marketing strategies. It utilized IoT technology to innovate the strategic marketing management of e-commerce enterprises, resulting in an average increase of 8.7% in sales and a return on investment (ROI) of 45%. Compared to traditional methods, IoT can improve the efficiency and effectiveness of marketing activities, and enterprises can be more flexible in conducting market experiments and quick trial and error. The application of IoT technology brings more opportunities to e-commerce enterprises.